2015
DOI: 10.1007/s10482-015-0570-8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and infection of Cladosporium, Fusarium, Epicoccum and Aureobasidium in withered rotten grapes during post-harvest dehydration

Abstract: Fungi like Cladosporium, Fusarium, Epicoccum and Aureobasidium can occur on withered grapes causing spoilage of passito wine. There is little or no information on the pathogenic role of these fungi. This study describes the isolation, incidence and identification of several isolates from different withered rotten grapes. Representative isolates grouped in several phenotypes were identified by phylogenetic analysis of internal transcribed spacer, actin or elongation factor gene sequences. Isolates of Cladospori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 38 publications
0
11
0
2
Order By: Relevance
“…In addition, all seaweed derived isolates identified in this study are facultative marine fungi and can be found in marine and terrestrial ecosystems. For instance, C. sphaerospermum [61], C. ramotenellum [62], P. brevicompactum [63], E. nigrum [62], C. rosea [64], and R. oryzae [65] are mainly known from terrestrial environments, but they are also found in deep sea (C. sphaerospermum) [66], Dead Sea water (C. ramotenellum, P. brevicompactum) [67], river sediments (C. rosea) [68], associated with marine sponges (E. nigrum, P. brevicompactum) [69,70], bryozoan Bugula sp. (R. oryzae) [71] or with seagrasses Posidonia oceanica (C. rosea) [72].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all seaweed derived isolates identified in this study are facultative marine fungi and can be found in marine and terrestrial ecosystems. For instance, C. sphaerospermum [61], C. ramotenellum [62], P. brevicompactum [63], E. nigrum [62], C. rosea [64], and R. oryzae [65] are mainly known from terrestrial environments, but they are also found in deep sea (C. sphaerospermum) [66], Dead Sea water (C. ramotenellum, P. brevicompactum) [67], river sediments (C. rosea) [68], associated with marine sponges (E. nigrum, P. brevicompactum) [69,70], bryozoan Bugula sp. (R. oryzae) [71] or with seagrasses Posidonia oceanica (C. rosea) [72].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation network in CTGP comprised 27 nodes and the average number, coefficient, heterogeneity, shortest path length, and average neighbor number were 0.778, 0.604, 86, and 3.185, respectively (Figure 6a). In CTGP, Alternaria (average RA > 10%) was a common plant and animal pathogen [16,44], which correlated negatively with unclassified_f__Enterobacteriaceae, un-classified_k__Fungi, and Naganishia. The addition of probiotics in PTGP decreased the number of nodes (24), coefficient (0.750), heterogeneity (0.407), shortest path length (70), and average neighbor number (2.917) of the correlation network (Figure 6b), which indicated few interactions in PTGP.…”
Section: Relationships Between Microflora and Their Physicochemical Characteristicsmentioning
confidence: 99%
“…Fusarium verticillioides has been detected from rotting grapes (Lorenzini & Zapparoli, 2015) and is a well-known fumonisin producer. Several other species of Fusarium can produce fumonisins, e.g.…”
Section: Fumonisins and Fungimentioning
confidence: 99%